Preparation and characterization study of some metal complexes of new ligand derived from benzothiazine (Journal of the College of Basic Education, 2023)
Anew ligand 2-(4-bromo phenyl)-4H-1,3-benzothiazine-4-one, has been prepared and characterized by (FTIR) spectroscopy, C.H.N.S elemental analysis. The new ligand has been used as chelating reagent to prepare Cr(III), Co(II), Mn(II), Cu(II) and Vo(IV), complexes were isolated, and characterized by (FTIR) ,(Uv-vis) spectra, flame atomic absorption technique, in addition to magnetic susceptibity, and conductivity measurements. The study of the nature of the complexes formed in ethanolic medium following the mole ratio method gave results which compound successfully with those obtained from isolated solid state studies as formula [ML2(H2o)2]Cl2 M: Mn(II), Co(II), Cu(II) and [CrL2Cl2] and [VoL2(H2O)]SO4 .